Promoting Mental Health Awareness in Schools: A Path Toward Holistic Education - Naila Javed (Global Journal of Multidisciplinary and Applied Sciences, 2023)
Mental health awareness in schools is crucial to fostering a positive educational environment that supports the well-being of students. Mental health problems among children and adolescents are on the rise globally, including in Pakistan, and often go unrecognized in the educational setting. This article explores the importance of promoting mental health awareness in schools, examining the role of educators, administrators, and parents in addressing mental health challenges. It discusses strategies for integrating mental health education into school curricula, providing support to affected students, and breaking the stigma associated with mental health issues. The article also offers recommendations for policy implementation at the national level to make mental health support a core component of educational practices in Pakistan.